2021
DOI: 10.3390/educsci11090462
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the COVID-19 Pandemic on Learning Quality and Practices in Higher Education—Using Deep and Surface Approaches

Abstract: This paper explores the student learning experience using technology as an e-learning tool during the COVID-19 pandemic. This article utilized qualitative methods to examine the quality of student learning using deep and surface approaches to understand what influences student engagement with technology. Interviews were conducted with 21 students from various academic majors using deductive content analysis to evaluate their responses. The findings show that technology increased student engagement with class d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 23 publications
1
22
0
2
Order By: Relevance
“…During the teaching process, it is possible to observe several phases: motivational (preparation of students for active learning), exposure (initial acquaintance of students with the new curriculum), fixation (initial repetition and confirmation of the curriculum), and diagnostic (testing of acquired knowledge, skills, and habits). Research on the impact of a pandemic on education is currently addressed by several authors and institutions within their conditions, for example [4][5][6][7][8][9][10][11].…”
mentioning
confidence: 99%
“…During the teaching process, it is possible to observe several phases: motivational (preparation of students for active learning), exposure (initial acquaintance of students with the new curriculum), fixation (initial repetition and confirmation of the curriculum), and diagnostic (testing of acquired knowledge, skills, and habits). Research on the impact of a pandemic on education is currently addressed by several authors and institutions within their conditions, for example [4][5][6][7][8][9][10][11].…”
mentioning
confidence: 99%
“…As the study takes place in a society in transition from a patriarchal order based on tribal networks [36] to one in which gender equity is gradually being inserted into its social fabric, education system, and workforce [18,[37][38][39], gender is examined to assess whether it differentiates students' responses to online instruction. In this socio-cultural context, women's newly acquired rights and opportunities may make them more determined to seek academic success [40], thereby expressing no diminished enrollment and learning or even growth. Alternatively, unforeseeable changes requiring a return to home confinement may make women less likely to adapt well to online instruction [41], thereby curtailing their enrollment and learning.…”
Section: Institutional Responsesmentioning
confidence: 99%
“…The lab sessions and lectures were delivered in a hybrid format with students spending half of their time online. It has been shown that during COVID-19, students felt disconnected from their peers and experienced loneliness [93]. As a result, it was important to create ample opportunities for students to engage with each other and practice their hands-on skills in a safe way.…”
Section: Safety For In-classroom Skill Checks Considerationsmentioning
confidence: 99%